Toward a Career Anchor Structure: An Empirical Investigation of Engineers - Wils, Laura; Wils, Thierry; Tremblay, Michel (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2010)
Contrary to Schein’s theory of career anchors, which rests on the dominance of a single career anchor, the present study proposes an original career anchor structure that captures multiple dominant anchors. The analysis of data from a sample of 880 Quebec engineers supports this reconceptualization based on a circular model of career anchors. The new dynamics of career anchors shows that several anchors are complementary (e.g., creativity and challenge) while others are conflictual (e.g., challenge and security). In particular, the correlational analysis at the axial level indicates that the “self-enhancement” pole (managerial competence, identity) is negatively correlated with the “self-transcendence” (service/dedication to a cause, technical competence), whereas the pole “openness to change” (challenge, entrepreneurial creativity) is negatively correlated with the “conservation” pole (security, lifestyle). These findings can lead to more research in career management.